2023
DOI: 10.1039/d2dt03599e
|View full text |Cite
|
Sign up to set email alerts
|

The binding of reducible N2 in the reaction domain of nitrogenase

Abstract: Promotional N2 (for the HD reaction of nitrogenase) binding at the exo-Fe2 position of FeMo-co allows reducible N2 (forming NH3) to diffuse in and bind exergonically at the endo coordination position of Fe2 or Fe6 in the central reaction domain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 88 publications
(132 reference statements)
1
7
0
Order By: Relevance
“…Additional clues in the nitrogenase story include inhibitor studies of MoFe-protein using carbon monoxide 39,40 , hydroxo 41 and selenium 42 , and provide powerful tools to prepare the stably trapped transient states and indicate the activation of N 2 occurs on a di-iron edge of FeMo-co. A recent study reported that the dissociated HS − species can be held within a protein cavity created by the reorientation of glutamine in V-nitrogenase 43 . Together with the facile exchange of all the three bridged sulfur sets, and the lability of the S2B towards ligand exchange found from experiments of site-selective incorporation of selenium in FeMo-co 42,44 , this sets up the possibility of partial or full dissociation of bridged S2B from FeMo-co as recently discussed by us and other theoretical work [45][46][47][48][49][50] .…”
Section: Introductionsupporting
confidence: 57%
“…Additional clues in the nitrogenase story include inhibitor studies of MoFe-protein using carbon monoxide 39,40 , hydroxo 41 and selenium 42 , and provide powerful tools to prepare the stably trapped transient states and indicate the activation of N 2 occurs on a di-iron edge of FeMo-co. A recent study reported that the dissociated HS − species can be held within a protein cavity created by the reorientation of glutamine in V-nitrogenase 43 . Together with the facile exchange of all the three bridged sulfur sets, and the lability of the S2B towards ligand exchange found from experiments of site-selective incorporation of selenium in FeMo-co 42,44 , this sets up the possibility of partial or full dissociation of bridged S2B from FeMo-co as recently discussed by us and other theoretical work [45][46][47][48][49][50] .…”
Section: Introductionsupporting
confidence: 57%
“…It is unclear whether the calculated binding is able to overcome the loss of translational entropy (may also be offset by H 2 evolution), which, based on gas-phase estimates, would be on the order of 10–15 kcal/mol. Recent work by Dance, however, has suggested a lower ∼4 kcal/mol entropic penalty based on N 2 binding from a diffusible position within the protein. , Future free energy simulations will hopefully be able to clarify this. The problem of DFT-method dependency on the results of FeMoco calculations is still far from being fully understood.…”
Section: Discussionmentioning
confidence: 97%
“…Recent work by Dance, however, has suggested a lower ∼4 kcal/mol entropic penalty based on N 2 binding from a diffusible position within the protein. 59 , 123 Future free energy simulations will hopefully be able to clarify this. The problem of DFT-method dependency on the results of FeMoco calculations is still far from being fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of entropy were not considered in this work. For N 2 binding energies one would expect a sizeable entropy penalty associated with the free energy of binding (B10 kcal mol À1 based on a gas phase estimate or B 4 kcal mol À1 if estimated from a diffusible position within the protein as suggested by Dance 49 ) but in this work our aim is not to derive realistic estimates of the free energy of binding. N 2 and H 2 were optimized in vacuum when calculating binding energies and dissociation energies.…”
Section: Computational Detailsmentioning
confidence: 96%
“…We note that other FeMoco studies from our group previously used TPSSh 18,28,30,34,36,52,55 while other researchers have utilized functionals such as TPSS, BP86, BLYP, PBE, B3LYP, B3LYP* and M06-2X. 9,[31][32][33]35,[37][38][39][40][41][42][43][44][45][46][47][48][49]58,[93][94][95][96][97][98][99] Here, we test whether density functionals that predict similar geometric structures of spin-coupled FeS systems (including E 0 FeMoco), predict similar energies of FeMoco E 3 isomers or not. We use the same QM/MM setup and same QM-region as in section B and every isomer was optimized with each functional to allow a fair comparison and to prevent bias.…”
Section: The Functional Dependency Of the Energy Rankingmentioning
confidence: 99%